2016
DOI: 10.1177/0266242615577708
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and firm performance in Indian SMEs: Universal and contingency perspectives

Abstract: This article explores entrepreneurial orientation (EO); this notion has received considerable theoretical and empirical attention in organizational research, emerging as one of the most widely accepted firm-level constructs in the literature. As knowledge in this area has expanded, researchers have delved into the contextual factors that influence the relationship between EO and organizational performance. With the goal of better understanding the circumstances under which pursuing entrepreneurial strategies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(181 citation statements)
references
References 122 publications
8
154
0
19
Order By: Relevance
“…This result is consistent with previous findings that found that organizational performance could be improved if the firms put a strong emphasis on innovativeness, riskiness, proactiveness, competitive aggressiveness, as well as on autonomy in response to market changes (Gupta & Batra, 2015;Walter et al, 2006). This is further supported by Jabeen and Mahmood (2014) who state that firms adopting a strong entrepreneurial orientation are willing to take risks and thus they can innovate quickly, which would result in more innovative products and leading to superior performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with previous findings that found that organizational performance could be improved if the firms put a strong emphasis on innovativeness, riskiness, proactiveness, competitive aggressiveness, as well as on autonomy in response to market changes (Gupta & Batra, 2015;Walter et al, 2006). This is further supported by Jabeen and Mahmood (2014) who state that firms adopting a strong entrepreneurial orientation are willing to take risks and thus they can innovate quickly, which would result in more innovative products and leading to superior performance.…”
Section: Discussionsupporting
confidence: 91%
“…A significant amount of strategy research has focused on the importance of top management (Hambrick & Mason, 1984) and entrepreneurial behavior (Covin & Slevin, 1989) in determining firm performance. It has been studied predominantly in its relation to the firm performance and has been consistently shown to be highly significant May Chiun Lo / Yin Chai Wang / Constance Rinen Justin Wah / T. Ramayah (Gupta & Batra, 2015). In a meta-analysis of 51 studies, Rauch et al (2009) …”
Section: 6entrepreneurial Orientationmentioning
confidence: 99%
“…The current study perspective is that, while EO determines specific strategic decisions and resource allocation for the organization (Wiklund & Shepherd, 2005), effective operationalization of EO requires alignment with operational context (Gupta & Batra, 2015). For example, firm entrepreneurial vision, capabilities and activities alone will not be enough to achieve success, unless there is a TQM philosophy in the organization (Sahoo & Yadav, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While recent studies support a positive relationship between entrepreneurial orientation and performance outcomes, they also point to a number of important mediating or moderating factors that may explain further how entrepreneurship is translated into organizational outcomes (e.g., Gupta & Batra, ; Semrau, Ambos, & Kraus, ; Stam & Elfring, ; Wales et al, ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%